If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3z-6=0
We simplify the equation to the form, which is simple to understand
3z-6=0
We move all terms containing z to the left and all other terms to the right.
+3z=0+6
We simplify left and right side of the equation.
+3z=+6
We divide both sides of the equation by 3 to get z.
z=2
| 21x+5= | | .01x=7 | | r^2+13r-30=0 | | 3x-3y-9x+7y= | | 23x-5= | | -6z=12 | | 3x^2=-21x-15 | | -5+4-10x=1 | | x^2+11x+19=0 | | 6x-b=-4x | | 112c=4(c-2)+4(2-8c) | | 4=m-9 | | 8-32=-4z | | x^2+8x+19=0 | | 9x^2+12xy+c=0 | | 12x+17= | | 5(6+c)=4(c-6) | | 56d^2-8d=0 | | -2X+8=4 | | 7z+2=-19 | | .8x^2+8x+19=0 | | 30+n=11 | | 4x+-12=-4 | | 4x+-12=4 | | -1+14x= | | 0.50x+0.20(40)=0.25(76) | | 8d-(25)=3d | | 4000g=48000 | | 0=-16x^2+9x+46 | | 7(w-4)=28 | | -4(x+7)+3=-25 | | 8x^2+8x+16=0 |